Maccera tasi' tradition of Palopo City fishermen (an anthropological study of communication) - Risky, Rheka; P, Efendi; Thaha, Hamdani (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background: Local traditions play a crucial role in maintaining the cultural identity of coastal communities. One such tradition is maccera tasi', a maritime ritual practiced by fishermen in Carede, Palopo City. Although rich in symbolic and spiritual meaning, this tradition has not been conducted since 2017, raising concerns over cultural sustainability. Aims: This study aims to explore the cultural meaning embedded in the maccera tasi' tradition and to investigate the socio-cultural reasons behind its cessation. Methods: Employing a descriptive qualitative design, this research utilized communication anthropology and ethnological approaches. Data were collected through in-depth interviews, observations, and documentation involving 15 informants from diverse stakeholder groups, including fishermen, traditional leaders, and cultural officials. Results: Findings revealed that maccera tasi' is perceived as an expression of gratitude, spiritual devotion, and social solidarity. Its discontinuation is attributed to shifting religious perspectives, lack of government support, and the impact of modernization. The tradition still resonates with the community’s collective memory, though younger generations increasingly question its relevance. Conclusion: The study highlights that maccera tasi' embodies more than ritual—it is a medium for symbolic communication, identity negotiation, and community cohesion. Its demise reflects broader societal transformations, particularly the friction between ancestral customs and evolving Islamic values. However, the potential for revitalization remains, provided there is collaborative effort from local stakeholders to repackage the tradition into a culturally appropriate and religiously acceptable format. Theoretically, the study contributes to communication anthropology by demonstrating how traditional symbols are not only preserved but reinterpreted in response to changing contexts. Practically, it urges inclusive cultural policy interventions to safeguard intangible heritage through adaptive, participatory, and context-sensitive strategies.